Commingled Art and Commingled Culture: The Benshi and 19th Century Japanese Film Culture - Carroll, Miranda (ARTiculate, 2024)
From 1896, when the first Kinetoscope was brought to Japan, to the early 1920s, all film screenings were accompanied by a live Japanese narrator called the benshi.Benshi stood to the left of the film screen and—speaking in melodious rhythms—provided narration, character impersonation, explanation of western exotica, and offered general commentary and critique for the then silent films. In late ninteenth-century Japan, film was not seen as an autonomous medium but rather as "commingled” media, comprised of vocal storytelling and projected motion pictures. This was in part due to long-standing Japanese theatrical traditions such as temple and itinerant etoki, the Japanese Buddhist practice in which monks use picture scrolls to expound Buddhist principles. Benshi performers drew upon such theatrical heritage to describe the foreign film apparatus, thereby fragmenting the filmic system of representation and instilling a distinct culture of critical independence in Japanese silent film audiences.This essay contributes to scholarly debates regarding “commingled” media, the juxtaposition of heterogeneous media, which is reflective of unique Japanese artistic culture. It provides a case study of Benshi Tokugawa Musei’s performance of the 1920 silent film The Cabinet of Dr. Caligari (Robert Wiene) recorded at the Kinokuniya Hall in Tokyo in 1968.7 This remaining work by Tokugawa Musei, a renowned benshi of the silent film era, offers insight into interactions between the benshi and silent film as it relates to Japanese traditions of “commingled” media.